2009
DOI: 10.4315/0362-028x-72.9.1848
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli O157 Prevalence in Different Cattle Farm Types and Identification of Potential Risk Factors

Abstract: Although the prevalence of Escherichia coli O157 on cattle farms has been examined extensively, the relationship between this pathogen and farm type has been established only rarely. A large-scale study was designed to determine the prevalence of E. coli O157 in the Flemish region of Belgium on farms of dairy cattle, beef cattle, mixed dairy and beef cattle, and veal calves. The effect of various factors on the occurrence at the pen level also was evaluated. In 2007, 180 farms were randomly selected based on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 41 publications
3
19
2
Order By: Relevance
“…These results are in agreement with the results of PCR screenings showing that the simultaneous presence of stx and eae genes was significantly more frequently detected in feces from young dairy bulls than in other categories. Overall, these results are consistent with the results of previous studies (54). Concerning the effect of age on STEC shedding, a Scotland investigation on 14,856 cattle fecal samples showed that an increased probability of a sampling group containing a STEC O157:H7-shedding animal was associated with larger numbers of 12-to 30-month-old finished cattle (55).…”
Section: Discussionsupporting
confidence: 91%
“…These results are in agreement with the results of PCR screenings showing that the simultaneous presence of stx and eae genes was significantly more frequently detected in feces from young dairy bulls than in other categories. Overall, these results are consistent with the results of previous studies (54). Concerning the effect of age on STEC shedding, a Scotland investigation on 14,856 cattle fecal samples showed that an increased probability of a sampling group containing a STEC O157:H7-shedding animal was associated with larger numbers of 12-to 30-month-old finished cattle (55).…”
Section: Discussionsupporting
confidence: 91%
“…A recent study compared prevalence of EHEC O157:H7 among 180 farms of different types (dairy, beef, mixed, and veal) in Belgium and found higher farm prevalence in dairy farms (61%) than in beef farms (23%), with an intermediate prevalence in mixed farms (44%); pen prevalence was also higher at dairy farms (Cobbaut et al, 2009). Since this is the first comparative study of this kind, which rigorously applied the same sampling and culturing techniques to all surveyed farms, it is not yet possible to conclude what factors may be responsible for the noticed differences.…”
Section: Transmission Of Ehec O157:h7mentioning
confidence: 99%
“…It was unexpected that stx was not detected at the dairy farming sites because stx2 was detected in fecal samples from both dairy and beef cattle farms used in this study (data not shown), and previous research has indicated STEC is shed from beef and dairy cattle [7,27]. However, it has been suggested that depending on their diet beef cattle may shed greater quantities of STEC compared to dairy cattle [3]. Overall qPCR detected approximately 50% less E. coli at the dairy farm sites compared to the beef cattle sites, and IDEXX enumeration of E. coli also indicated that there were lower levels of E. coli at dairy cattle sites (DC1 and DC2).…”
Section: Discussionmentioning
confidence: 57%
“…This outbreak was caused by consumption of poorly cooked ground beef in a fast-food restaurant chain in the western US From 1982 to 2002, a total of 350 E. coli O157:H7 outbreaks were reported in 49 US states, from which 325 outbreaks included a number of deaths [1]. Although the Shiga-toxin gene is found in all enterohemorrhagic E. coli (STEC), serotype O157:H7 alone is responsible for more than 73,000 cases of disease per year in the US, and it has been implicated in 250 deaths [1,2]; Cattle and other ruminants are natural reservoirs of E. coli O157:H7 that can introduce pathogenic E. coli into the environment through fecal shedding [3][4][5][6]. Estimates of occurrence vary, but it appears that both dairy herds and beef feedlots can have animals carrying STEC including E. coli O157:H7 [6,7].…”
Section: Introductionmentioning
confidence: 99%